2009
DOI: 10.5324/nje.v18i2.31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prescribing quality in nursing homes based on drug-specific indicators: The Bergen district nursing home (BEDNURS) study

Abstract: Objectives:To examine prescribing quality among nursing home patients. Methods: A cross sectional study in 23 nursing homes, based on drug charts. The evaluation of prescribing quality was based on selected drug-specific indicators established by the Swedish National Board of Health and Welfare. Logistic regression analysis was used to examine associations between prescribing indicators and predictors related to patient (age, gender, drug number) and institution (nurse and physician staff time) characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…The prevalence of PIMs in NHs in this study was lower compared with that in previous NH studies in Norway and other Nordic countries regarding long‐acting benzodiazepines, anticholinergic drugs, and multiple psychotropic drugs . However, concomitant use of three or more psychotropic drugs in our study was more prevalent than reported in previous Norwegian cross‐sectional studies in the community and in NHs…”
Section: Discussioncontrasting
confidence: 91%
“…The prevalence of PIMs in NHs in this study was lower compared with that in previous NH studies in Norway and other Nordic countries regarding long‐acting benzodiazepines, anticholinergic drugs, and multiple psychotropic drugs . However, concomitant use of three or more psychotropic drugs in our study was more prevalent than reported in previous Norwegian cross‐sectional studies in the community and in NHs…”
Section: Discussioncontrasting
confidence: 91%
“…In this study, about 16% of the patients who used anti‐dementia drugs also used antipsychotics concomitantly. Considering that this sample mainly consisted of outpatients, these figures seem in line with two Norwegian studies from different nursing homes, finding that 16–26% of the patients used antipsychotics . The present sample may include patients with psychiatric disorders that already were taking antipsychotic drugs as part of their main treatment regime before developing dementia.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, younger age has been associated with a higher rate of PIMs. 11,22,23,28 The oldest residents may have fewer comorbidities, reflecting a "survival of the fittest." 22,23 Furthermore, GPs may be more cautious in prescribing because they see very old residents as frailer.…”
Section: Discussionmentioning
confidence: 99%
“…11,22,23,28 The oldest residents may have fewer comorbidities, reflecting a "survival of the fittest." 22,23 Furthermore, GPs may be more cautious in prescribing because they see very old residents as frailer. 15,22 However, many studies in NHs have not demonstrated this association.…”
Section: Discussionmentioning
confidence: 99%